2018
DOI: 10.1002/pros.23709
|View full text |Cite
|
Sign up to set email alerts
|

NPRL2 enhances autophagy and the resistance to Everolimus in castration‐resistant prostate cancer

Abstract: NPRL2 may act as a pro-growth factor in PCa. The high levels of NPRL2 expression in CRPC promote resistance to EVS by enhancing autophagy. NPRL2 may be a new therapeutic target for intervention of CRPC and a biomarker for predicting resistance to EVS in CRPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…Many studies have shown that multiple oncogenes promote PCa cell proliferation, migration, invasion, and inhibiting apoptosis through activating the PI3K-AKT-mTOR signaling pathway [24]. Chen et al found that the high levels of NPRL2 gene expression in prostate cancer cells promote resistance to EVS (an inhibitor of the mTOR) by enhancing autophagy [25]. In addition, TSC1 was significantly associated with DFS in PCa, which is an essential component of the PI3K/ AKT/mTOR signaling pathway [26].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that multiple oncogenes promote PCa cell proliferation, migration, invasion, and inhibiting apoptosis through activating the PI3K-AKT-mTOR signaling pathway [24]. Chen et al found that the high levels of NPRL2 gene expression in prostate cancer cells promote resistance to EVS (an inhibitor of the mTOR) by enhancing autophagy [25]. In addition, TSC1 was significantly associated with DFS in PCa, which is an essential component of the PI3K/ AKT/mTOR signaling pathway [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that the resistance of cancer cells to a variety of anticancer drugs can increase via upregulation of autophagy [ 118 , 119 ]. Autophagy is a protective mechanism in cancer cells undergoing anticancer therapy.…”
Section: Autophagy As Drug-resistant Factor Of Tumorsmentioning
confidence: 99%
“…Similar findings have been demonstrated in a range of other cancers, including estrogen receptor-positive breast cancer where autophagy inhibition can re-sensitise breast cancer cells to tamoxifen [92] . In prostate cancer, high levels of nitrogen permease regulator-like 2, a tumour suppressor candidate gene, can cause resistance to Everolimus by enhancing autophagy via mTOR [93] .…”
Section: Autophagy and Drug Resistancementioning
confidence: 99%